Investigating Gender and Sexuality in the ESL classroom: Raising publishers', teachers' and students' awareness - Pakuła, Łukasz Piotr; Pawelczyk, Joanna (My University, 2013)
A promotional brochure of a project run by Faculty of English (AMU) and Lancaster University, and funded by the British Council.
project website: http://www.wa.amu.edu.pl/eflproject
Keywords: Critical Pedagogies; Language, Gender, Sexuality; Queer Pedagogies; Critical Discourse Analysis